2010
DOI: 10.3329/jhpn.v28i4.6044
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Neonatal Deaths in a Rural Subdistrict of Bangladesh: Implications for Intervention

Abstract: The study assessed the timing and causes of neonatal deaths in a rural area of Bangladesh. A population-based demographic surveillance system, run by the International Centre for Diarrhoeal Disease Research, Bangladesh, recorded livebirths and neonatal deaths during 2003-2004 among a population of 224,000 living in Matlab, a rural subdistrict of eastern Bangladesh. Deaths were investigated using the INDEPTH/World Health Organization verbal autopsy. Three physicians independently reviewed data from verbal autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
69
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 24 publications
13
69
4
Order By: Relevance
“…3 Most neonatal deaths occur within the first week of life. 4 An estimated 35.1% of neonatal deaths are caused by prematurity, 23.3% by intrapartumrelated complications (birth asphyxia), and 26.9% by infection-related causes (sepsis/meningitis, pneumonia, tetanus, and diarrhea). 3 An important component of reducing maternal mortality and morbidity and intrapartum-related neonatal deaths is to increase the availability, quality, and demand for skilled care at birth.…”
Section: Introductionmentioning
confidence: 99%
“…3 Most neonatal deaths occur within the first week of life. 4 An estimated 35.1% of neonatal deaths are caused by prematurity, 23.3% by intrapartumrelated complications (birth asphyxia), and 26.9% by infection-related causes (sepsis/meningitis, pneumonia, tetanus, and diarrhea). 3 An important component of reducing maternal mortality and morbidity and intrapartum-related neonatal deaths is to increase the availability, quality, and demand for skilled care at birth.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests the use of methylene blue as a new treatment to prevent or decrease retinal damage in the context of ischemic proliferative retinopathy. retina; nitric oxide; ischemic proliferative retinopathy; methylene blue; angiogenesis PERINATAL ASPHYXIA (PA) is one of the most severe problems in perinatology services across the world (9,15,23,27). PA generates a transient global hypoxia-ischemia status that damages the brain, spinal cord, and retina (14, 17, 39, 52).…”
mentioning
confidence: 99%
“…Among them, 39 were in the OPD group and 27 in the IPD group. A total of seven patients were excluded (OPD 2 and IPD 5) due to reasons such as lost to follow-up (4), left against medical advice (LAMA) (1), death (1) and referred to a higher centre (1). Finally, data were analysed for 59 neonates (OPD 37 and IPD 22) (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that sepsis and pneumonia were the causes of death in 27% of newborns. 1 The early and efficient diagnosis of neonatal sepsis remains a difficult task due to delayed development of signs and symptoms. Early diagnosis and treatment with suitable antibiotics are usually started in hospital.…”
Section: Introductionmentioning
confidence: 99%